Farmer Innovativeness and Hybrid Maize Diffusion in Thailand - Sutthiporn Poolsawas; Orachos Napasintuwong (Journal of International Agricultural and Extension Education, 2013)
Hybrid maize in Thailand is one example of successful technology dissemination in a developing country. The first hybrid maize variety was released in 1982 by a public research institute, but did not become rapidly adopted until the privatization of the seed market in the early 1990s.Previous studies on the adoption of hybrid maize in Thailand mainly analyzed factors influencing the adoption decision, but none evaluated the timing of the adoption process. This study reveals the diffusion pattern of hybrid maize varieties and categorizes farmers by the time of adoption. It was hypothesized that different categories of farmers would differ in their innovativeness. The results show that the distribution of hybrid maize adoption in Thailand approaches a normal distribution consistent with the literature. Younger and less educated farmers with larger households and farm size tended to adopt hybrid maize faster than others. Furthermore, social activities, extension services, private company promotion programs and access to information on hybrid varieties played important roles in the adoption lag
Keywords: Technology Diffusion; Technology Adoption; Hybrid Maize; Innovativeness; Communication Channels